Investigating the Role of Genetic Polymorphism in the Exon 3 of ATG16L1 Gene in T2DM Patients: A Pilot Study - Alnaji, Haider; Al-Mhanaa, Haider (Biomedical Sciences and Clinical Medicine, 2025)
Objective Diabetes mellitus (DM) is a metabolic disease characterized by persistently high blood sugar levels and has several potential causes. We aimed to find out whether there are any single nucleotide polymorphisms in a particular region of the ATG16L1 gene which are linked to type 2 diabetes. Methods A total of forty participants were included in this study; 20 were part of the patient group and had type 2 diabetes mellitus (T2DM), while 20 were part of the healthy control group. High-resolution melt (HRM) analysis was used for genotyping along with sequencing for confirmation of the results. Results The melting behavior showed consistent DNA sequence in the exon 3 of the ATG16L1 gene in both the patient and the healthy control groups in the study. Conclusions The ATG16L1 gene does not include any SNPs in the exon 3 region associated with type 2 diabetes. However, further studies are needed to determine the role of the autophagy gene in T2DM.